An overlooked case for a century: taxonomy and systematics of a new Iberian species of Eumerus Meigen, 1822 (Diptera, Syrphidae) - Aguado-Aranda, Pablo; Ricarte, Antonio; Nedelković, Zorica; Marcos-García, Ángeles (European Journal of Taxonomy, 2022)
The hoverfly genus Eumerus Meigen, 1822 (Eristalinae: Merodontini) comprises 250+ described species, of which 36 are reported from the Iberian Peninsula. The high species diversity linked to the low degree of morphological differentiation between some species, which is even lower in females, leads to a high taxonomic complexity in this genus. The aim of this work is to confirm the morphological and molecular validity of an undescribed species of Eumerus, which is widespread in the Iberian Peninsula. The new species is described and compared with similar species. The genitalia of the new species are similar to those of Eumerus clavatus Becker, 1923 and Eumerus uncipes Rondani, 1850, but also share some features with Eumerus nudus Loew, 1848. The COI-5’ barcode is provided for the new taxon and analysed together with those of other named Eumerus sequences/species publicly available online. In the light of the morphology and barcoding data, the systematic position of the new species is discussed.